Improvement of EIGRP protocol routing algorithm based on information security metrics - Снегуров, А. В.; Чакрян, В. Х. (Харьковский национальный университет радиоэлектроники, 2015)
Routing algorithm improvement in the ways of unequal value for the EIGRP protocol with the introduction of such a measure as the risk of information security into the metric is proposed in this paper. It is proposed to evaluate the risk of information security using the methodology of the NIST CVSS standard and the theory of information systems survivability
Keywords: information security; routing protocols; risk of information security; EIGRP; metric